The Microfinance Business Model : Enduring Subsidy and Modest Profit - Cull, Robert; Demirguc-Kunt, Asli; Morduch, Jonathan (World Bank, Washington, DC, 2016)
Recent evidence suggests only modest social and economic impacts of microfinance. Favorable cost-benefit ratios then depend on low costs. This paper uses proprietary data on 1,335 microfinance institutions between 2005 and 2009, jointly serving 80.1 million borrowers, to calculate the costs of microfinance and other elements of the microfinance business model. It calculates that on average, subsidies amounted to $132 per borrower, but the distribution is highly skewed. The median microfinance institution used subsidies at a rate of just $26 per borrower, and no subsidy was used by the institution at the 25th percentile. These data suggest that, for some institutions, even modest benefits could yield impressive cost-benefit ratios. At the same time, the data show that the subsidy is large for some institutions. Counter to expectations, the most heavily-subsidized group of borrowers is customers of the most commercialized institutions, with an average of $275 per borrower and a median of $93. Customers of nongovernmental organizations, which focus on the poorest customers and women, receive a far smaller subsidy: the median microfinance nongovernmental organization used subsidy at a rate of $23 per borrower, and subsidy for the nongovernmental organization at the 25th percentile was just $3 per borrower.